Design and Simulation for Disk-type Magnetorheological Fluid Transmission Device - Zhang Qiuxiang; Ren Yankun; Wang Lifeng; Liu Xinhua; Hu Yuan (Jixie chuandong)
The magnetorheological fluid transmission device power transmission mechanism is analyzed according to the Bingham model,and a disk- type magnetorheological fluid transmission device is designed. By using finite element analysis software Ansoft Maxwell,the magnetic circuit design and magnetic field simulation are carried out and the magnetic field distribution nephogram is obtained. A magnetic field tester is built,on which the magnetic field is tested. This transmission device is able to meet the working requirements,and the foundation for the next experiment is laid.